MANAGE: A Case of HRD in Government - Vikram Singh,; B.D. Tripathi, (Journal of Agricultural Extension Management, 2025)
The National Institute of Agricultural Extension Management (MANAGE) is an apex level autonomous body set up in 1987 under the Ministry of Agriculture, Government oflndia. It is the Indian response to the challenges of management in a rapidly growing and diverse agricultural sector. An organization like MANAGE has three important elements which have a direct bearing on the performance of the individual’s viz., structure, culture and processes. Structures in the organizations are generally given and the amendments in them are rarely done as it involve decisions at the topmost level. However, bringing changes in the culture and processes, are well within the authority of head of the organization and also at the command of the individuals at different levels. Realizing this fact, in MANAGE, lot of innovative initiatives are taken with an eye on positive changes and performance raise in the organization. This process of change aims at becoming responsive institution ready to meet the demands and challenges of the 21st century organization